Improvement of functional outcome for patients with newly diagnosed grade 2 or 3 gliomas with co-deletion of 1p/19q – IMPROVE CODEL: the NOA-18 trial - A. Wick; A. Sander; M. Koch; M. Bendszus; S. Combs; T. Haut; A. Dormann; S. Walter; M. Pertz; J. Merkle-Lock; N. Selkrig; R. Limprecht; et al. (BMC Cancer, 2022)
Abstract Background Given the young age of patients with CNS WHO grade 2 and 3 oligodendrogliomas and the relevant risk of neurocognitive, functional, and quality-of-life impairment with the current aggressive standard of care treatment, chemoradiation with PCV, of the tumour located in the brain optimizing care is the major challenge. Methods NOA-18 aims at improving qualified overall survival (qOS) for adult patients with CNS WHO grade 2 and 3 oligodendrogliomas by randomizing between standard chemoradiation with up to six six-weekly cycles with PCV and six six-weekly cycles with lomustine and temozolomide (CETEG) (n = 182 patients per group accrued over 4 years) thereby delaying radiotherapy and adding the chemoradiotherapy concept at progression after initial radiation-free chemotherapy, allowing for effective salvage treatment and delaying potentially deleterious side effects. QOS represents a new concept and is defined as OS without functional and/or cognitive and/or quality of life deterioration regardless of whether tumour progression or toxicity is the main cause. The primary objective is to show superiority of an initial CETEG treatment followed by partial brain radiotherapy (RT) plus PCV (RT-PCV) at progression over partial brain radiotherapy (RT) followed by procarbazine, lomustine, and vincristine (PCV) chemotherapy (RT-PCV) and best investigators choice (BIC) at progression for sustained qOS. An event concerning a sustained qOS is then defined as a functional and/or cognitive and/or quality of life deterioration after completion of primary therapy on two consecutive study visits with an interval of 3 months, tolerating a deviation of at most 1 month. Assessments are done with a 3-monthly MRI, assessment of the NANO scale, HRQoL, and KPS, and annual cognitive testing. Secondary objectives are evaluation and comparison of the two groups regarding secondary endpoints (short-term qOS, PFS, OS, complete and partial response rate). The trial is planned to be conducted at a minimum of 18 NOA study sites in Germany. Discussion qOS represents a new concept. The present NOA trial aims at showing the superiority of CETEG plus RT-PCV over RT-PCV plus BIC as determined at the level of OS without sustained functional deterioration for all patients with oligodendroglioma diagnosed according to the most recent WHO classification. Trial registration Clinicaltrials.gov NCT05331521 . EudraCT 2018–005027-16.